Performance Enhancement of a 2-Cylinder Engine with Naphthalene Addition to RON 90 - Hariyadi, Muhammad Arif; Aspiyansyah, Aspiyansyah; Harianto, Agus; Pratama, Rubi (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2020)
The octane number of fuel is crucial for the performance of a two-cylinder gasoline engine. This study aims to enhance the octane number by using naphthalene. The method involved mixing RON 90 gasoline with naphthalene to evaluate engine performance parameters, including torque, power, specific fuel consumption, and efficiency. The results indicate that adding 20 mg of naphthalene to 1 liter of RON 90 gasoline optimizes the performance of a two-cylinder gasoline motorcycle engine.